PEDAGOGICAL DECISIONS AMONG VOCATIONAL COLLEGE TEACHER IN MALAYSIA - Jailani Md Yonus; Siti Nur Kamariah Rubani; Faizal Amin Nur Yunus; Hashima Hamid; Sri Sumarwati (AL-ASASIYYA: Journal Of Basic Education, 2019)
To achieve the objective of vocational education, teachers are required to use a variety of teaching and learning methods to improve student achievement. Cultural differences in a country can influence the pattern of thinking and attitudes in implementing an educational system. This study aims to identify pedagogical decisions based on “theory”, “practical” and “technical drawing”, used by Vocational College teachers in Malaysia. This study is a survey of quantitative studies. This research instrument is a questionnaire which is an adaptation of Lucas (2014). The results of the pilot study found that overall questionnaire items had the Alpha Cronbach value of 0.87 - 0.90. It can be concluded that the questionnaire in this study is valid and reliable. The respondents of this study were selected using a random sampling method consisting of 312 vocational college teachers in Malaysia. The data in this study have been analyzed using the Statistical Packages for Social Science (SPSS) version 21. Based on “theory”, “practical” and “technical drawing”, respondents prefer “facilitative” for “Role of Teacher” element, “authentic” for “Nature of Knowing”, “Bell bound time” for “Content of Curriculum”, limited to specified content “for element” Organization of Space element, “individually” for “Approach to Task” element, “explicit” for “Visibility of Processes” element, “face to face” for “Attitude to Knowledge” element, and “instruction monitor” for “Role of Learner” element. However, based on “theory” and “practical” respondents prefer “questioning” for “Organization of Time” element and “workshop” for “Proximity to Teacher” element. In addition, based on “technical drawing” respondents prefer “certain” for “Organization of Time” element and “classroom” for “Proximity to Teacher” element.